A Phenomenological Exploration Impact of Work-Life Balance and its Implications for the Creativity and Productivity of Gen Z Entrepreneurs - Christy, Albertha Septya; Prawihatmi, Chatarina Yekti (Journal of Management Economic and Financial, 2025)
Indonesian Gen Z workers face challenges in achieving a Work-Life Balance (WLB) due to digitalization, flexibility, and dynamic socio-economic interactions. The purpose of this study is to investigate how Gen Z workers understand and manage their work-related lives and how WLB affects their creativity and productivity. The methodology employed is transcendental phenomenology, which analyzes the lived experiences of Gen Z business owners (both active and passive), providing a key piece of information in the field of business psychology. Open questionnaires and semi-structured interviews are used to gather the data, which is then manually coded thematically according to Moustakas's (1994) methodology. The results indicate that WLB is a kind of self-regulation strategy that enhances intrinsic motivation and creative productivity. The three main themes discussed are (1) balance as self-regulation and productivity strategy, (2) the digital paradox between flexibility and technology, and (3) the maturity of experience in observing life balance. This integrates the theories of Resource-Based View (RBV), Self-Determination Theory (SDT), and Componential Theory of Creativity, stating that WLB is a strategic psychological approach that increases creativity and productive work.